Effect of Wood Flours on Moulding Sand Properties - Kumara, Pavana; Bhat, Vijendra; *, Ranganatha; Banagara, Ashok (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Casting process involves number of variables which have to be controlled to get sound product (defect free). The sand moulds are used in most casting techniques because of their simplicity and ease of handling. Sand selection and deciding about its composition is considered as critical task in casting process. The right amount of silica sand (base sand) combined with clay (binder), water (moisture) along with additives impart required qualities in the mould are treated as basic ingredients of the moulding sand. This paper presents the results of the work carried out using different wood flours as an additive with the moulding sand mixture. The effect of four wood flours viz. Jack fruit, Mango, Acasia and teak on different properties of mould like Permeability number, Green and Compression strength were analysed. It was observed that the wood flours have significant effect on above said properties.